Uncovering the biogeography of the microbial commmunity and its association with nutrient metabolism in the intestinal tract using a pig model - Song, Yuanyuan; Chen, Kai; Lv, Lu; Xiang, Yun; Du, Xizhong; Zhang, Xiaojun; Zhao, Guangmin; Xiao, Yingping (Frontiers in Nutrition, 2022)
The gut microbiota is a complex ecosystem that is essential for the metabolism, immunity and health of the host. The gut microbiota also plays a critical role in nutrient absorption and metabolism, and nutrients can influence the growth and composition of the gut microbiota. To gain a better understanding of the relationship between the gut microbial composition and nutrient metabolism and absorption, we used a pig model by collecting the contents of the different intestinal locations from six pigs to investigate microbial composition in different intestinal locations based on 16S rRNA gene sequencing and the concentrations of short-chain fatty acids (SCFAs), amino acids, fat, and crude ash in different intestinal locations using gas chromatography and chemical analysis. The results showed that the richness and diversity of intestinal microbial communities gradually increased from the small intestine to the large intestine. The relative abundance of Proteobacteria was higher in the jejunum and ileum, whereas the proportion of Firmicutes was higher in the cecum and colon. The concentrations of SCFAs were higher in the cecum and colon (P<0.05). The concentrations of amino acids were higher in the small intestine than in the large intestine, while the amino acid content was significantly higher in the ascending colon than in the transverse colon and descending colon. A correlation analysis revealed that Ruminococcaceae (UCG-004, UCG-005), Coriobacteriaceae_uncultured, [Eubacterium]hallii group, Mogibacterium, Pseudobutyrivibrio, Marvinbryantia, and Lachnospiraceae AC2044 group had a higher positive correlation with SCFAs. The genera [Eubacterium] hallii group, Lachnospiraceae AC2044 group, Ruminococcaceae UCG-005, Coriobacteriaceae_uncultured, and Mogibacterium had a positive correlation with crude ash and fat, and the genera Marvinbryantia, Terrisporobacter, Romboutsia, [Eubacterium] hallii group, Ruminococcaceae UCG-005, Lachnospiraceae AC2044 group, Coriobacteriaceae_uncultured and Mogibacterium had a negative correlation with amino acids in different gut locations of pigs. In conclusion, Ruminococcaceae UCG-005, [Eubacterium] hallii group, Lachnospiraceae AC2044 group, Coriobacteriaceae_uncultured and Mogibacterium were associated with the metabolism of SCFAs, amino acids, fat and crude ash. These findings may serve as fundamental data for using nutrient metabolism to regulate human and animal gut microbes and health and provide guidance for exploring host-microbe bidirectional interaction mechanisms and driving pathways.